Hybrid Multi-User Equalizer for Massive MIMO Millimeter-Wave Dynamic Subconnected Architecture - Roberto Magueta; Daniel Castanheira; Adao Silva; Rui Dinis; Atilio Gameiro (IEEE Access, 2019)
This paper proposes a hybrid multi-user equalizer for the uplink of broadband millimeter-wave massive multiple input/multiple output (MIMO) systems with dynamic subarray antennas. Hybrid subconnected architectures are more suitable for practical applications since the number of required phase shifters is lower than in fully connected architectures. We consider a set of only analog precoded users transmitting to a base station and sharing the same radio resources. At the receiver end, the hybrid multi-user equalizer is designed by minimizing the sum of the mean square error (MSE) of all subcarriers, considering a two-step approach. In the first step, the digital part is iteratively computed as a function of the analog part. It is considered that the digital equalizers are computed on a per subcarrier basis, while the analog equalizer is constant over the subcarriers and the digital iterations due to hardware constraints. In the second step, the analog equalizer with dynamic antenna mapping is derived to connect the best set of antennas to each radio frequency (RF) chain. For each subset of antennas, one antenna and a quantized phase shifter are selected at a time, taking into account all previously selected antennas. The results show that the proposed hybrid dynamic two-step equalizer achieves a performance close to the fully connected counterpart, although it is less complex in terms of hardware and signal processing requirements.